Diacerein-induced interleukin-1β deficiency reduces the inflammatory infiltrate and immunoexpression of matrix metalloproteinase-8 in periodontitis in rat molars - Silva, Renata Cristina Lima [UNESP]; Sasso-Cerri, Estela [UNESP]; Cerri, Paulo Sérgio [UNESP] (Wiley, 2022)
Background: Periodontitis is an immunoinflammatory disease that involves the release of cytokines and enzymes, including interleukin-1 (IL-1) and matrix metalloproteinases (MMPs). Diacerein is an anti-IL-1 drug used for the treatment of osteoarthritis. The aim of the study was to evaluate whether diacerein suppresses the inflammatory reaction and reduces the collagen degradation in the gingival connective tissue in periodontitis. Methods: Fifty-four male rats were distributed into three groups (n = 18 animals/group): 1) periodontitis + diacerein group (PDG), 2) periodontitis + saline group (PSG) and control Group (CG; without treatment). Periodontitis was induced for 7 days in the upper right first molars; after 7 days, the animals of PDG received 100 mg/kg of diacerein while in PSG, the animals received saline solution for 7, 15, and 30 days. The animals were killed and fragments of maxilla containing the right molars were processed for paraffin embedding. In hematoxlin & eosin-stained sections, the volume density of inflammatory cells (VvIC) and fibroblasts (VvFb) in the gingival mucosa, the distances between the junctional epithelium (JE) to the cemento-enamel junction (CEJ) and the CEJ to the alveolar process crest (AP) were obtained. The number of IL-1β‒ and MMP-8‒immunolabeled cells, and collagen content in the gingival mucosa were computed. Data were subjected to two-way analysis of variance and Tukey post-test (P ≤ 0.05). Results: The PDG and PSG rats showed a significant increase in the distances of JE-CEJ and CEJ-AP. In all periods, the VvIC, the number of IL-1β‒ and MMP-8‒immunolabeled cells was significantly lower in PDG than in PSG while the collagen content was significantly greater in PDG than PSG. At 30 days, significant differences in the IL-1β immunoexpression, collagen content, and in the MMP-8 immunostaining were not seen between PDG and CG groups. Conclusions: Our results show an inhibitory effect of diacerein on IL-1β in the inflamed gingival mucosa of rat molars, decreasing the inflammatory infiltrate and immunoexpression of MMP-8, and restoring the collagen content.
Keywords: cytokines; gingiva; interleukin-1; matrix metalloproteinases; periodontitis